2017
DOI: 10.21834/aje-bs.v2i2.174
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between Planning and Environmental Psychology: An application of sense of place for visioning of public policy

Abstract: This paper aimed to explore a new methodology for vision making and sharing of a local municipality. The study explored using the residents' sense of place as a key element of the vision for the local town in order to ease the conflict or discomfort that can arise among diverse populations of merged municipalities. A method named Visioning with Sense of Place was developed for this study. Analyses indentified that the visioning process stimulated the participants to develop a broader sense of place with the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Occupants only serve as a consumer in the commercial center and not as a producer. Shirotsuki et al (2010) suggested developing the concept of sense of place in public spaces so that residents also participate in proposed the policy for the residential area. In Figure 5 appears that there are 66% of respondents who were satisfied with the facilities provided at the commercial center, followed by 20% feel quite satisfied and only 14% were dissatisfied.…”
Section: Resultsmentioning
confidence: 99%
“…Occupants only serve as a consumer in the commercial center and not as a producer. Shirotsuki et al (2010) suggested developing the concept of sense of place in public spaces so that residents also participate in proposed the policy for the residential area. In Figure 5 appears that there are 66% of respondents who were satisfied with the facilities provided at the commercial center, followed by 20% feel quite satisfied and only 14% were dissatisfied.…”
Section: Resultsmentioning
confidence: 99%
“…Such methods encourage community participation and knowledge exchange which then play an important role in project planning, implementation and sustainability. Stakeholder-driven data acquisition with an emphasis on collaboration and the incorporation of local knowledge has been cited as a key feature to the success and sustainability of local planning and development projects (Jorgensen & Stedman, 2001; Kianicka et al, 2006;Vong et al, 2016;Wells et al, 2016;Shirotsuki et al, 2017).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…PGIS approaches have the unique ability to convey a more inclusive picture of humanenvironmental interactions by representing knowledge of community members that may escape conventional scientific data collection techniques (Savitsky et al, 1999;Dragićević , 2004;Hasse & Milne, 2005;Talen & Shah, 2007;Aditya, 2010;Sutcliffe & Wilson, 2011;Coulton et al, 2013;Boschmann & Cubbon, 2014;Loureiro, 2014;Ricker & Hedley, 2014;Shirotsuki et al, 2017). The representation of local knowledge is important since many human geographers view "place" as a geographical entity with subjective meanings (McCall, 2004;Hawthorne et al, 2008;Hawthorne et al, 2015;Vong et al, 2016;Ghose & Welcenbach, 2018).…”
Section: Pgis Applications For Flood Managementmentioning
confidence: 99%
“…The location of production and manufacturing should be based on the economic strategies plans and directions as to produce more job vacancies especially in the rural areas. Shirotsuki, M., et al, (2010) stated that "resource allocation has been one of the residents' biggest concerns; more precisely, they were concerned about allocation of financial". Hence, placement of sectors in the rural areas should be based on the potential of existing resources which may helps to revive the economic development in that area.…”
Section: Improvement In the Location Of Jobs Opportunities Based On Dmentioning
confidence: 99%
“…Hence, placement of sectors in the rural areas should be based on the potential of existing resources which may helps to revive the economic development in that area. Not only that, Shirotsuki, Otsuki & Sonoda (2010) and Ujang (2010 agreed that individual and society development were attached to their placement. Focus development area have to precise especially in outskirts as to cater the needs and demands of local labor , indirectly provide more jobs opportunity to those who're living in the rural area as most of them avoiding working outside of their living area.…”
Section: Improvement In the Location Of Jobs Opportunities Based On Dmentioning
confidence: 99%